THE DIFFERENCE OF STUDENT ACHIEVEMENT USING MODEL PROBLEM BASED LEARNING MODEL WITH PROJECT BASED LEARNING MODEL MUSHROOMS MATERIALS IN CLASS X SMA NEGERI 16 MEDAN - Willy Novita; Martina Restuati; Sri Handayani (Universitas Negeri Medan, 2016)
The aim of this research was to know the diference of student’s learning result taught by problembased learning model with project based learning model in fungi material in class X SMA Negeri 16 Medan. Anexperimental research where the population is all students in X SMAN 16 Medan MIA consisting of four classeswith the sample two classes. Each class numbered 40 students, so the number of samples in this study were 80students. Prerequisite test of analysis consisted of normality test and homogeneity test. The result was showedthat all groups were in normally distribution and the samples have same of variance (homogeneous). Theanalysis of hypothesis test used t that showed t count= 0.28 <ttable = 1.66 with df = 78 and a significance level0.05. It can be concluded that there is no significant difference between the learning outcomes of studentswho were taught using problem based learning model with projeck based learning in Mushrooms materials inclass X SMA Negeri 16 Medan.Keywords: Problem based learning, project based learning, student learning outcomes, mushrooms